Sosialisasi Mengenai Pelibatan dan Pemberdayaan Karyawan Pada UMK Makanan Keripik Azizah - Fenia, Selvi Zola; Nadila, Nia; Parwati, Tri Ayu (LPPM Universitas Dharma Andalas, 2024)
Employees in a company are not only part of carrying out the company's functions, but are valuable assets in the company's success. In order to realize the success of the company, the company's valuable assets, namely employees, need to have full involvement in the company. Companies must also encourage employee involvement in their work so that they can improve company performance. Kerupuk Azizah was formed in 2009 which started as a group of mothers when there was a social gathering, someone proposed a wish or idea for this business which initially was just a group effort. The aim of this activity is to provide knowledge regarding employee involvement and empowerment in the form of outreach to Azizah cracker workers located at Jalan Indarung, Lubuk Kilangan District, Padang City.